2014
DOI: 10.1016/j.ygyno.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and ovarian cancer: More complex than just increasing risk

Abstract: Objective Diabetes mellitus (DM) is a risk factor for endometrial cancer and is associated with poorer outcomes in breast and colon cancers. This association is less clear in epithelial ovarian cancer (EOC). We sought to examine the effect of DM on progression-free (PFS) and overall survival (OS) in women with EOC. Methods A retrospective cohort study of EOC patients diagnosed between 2004 and 2009 at a single institution was performed. Demographic, pathologic and DM diagnosis data were abstracted. Pearson c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
1
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 39 publications
4
54
1
2
Order By: Relevance
“…This was partially attributed to co-morbidities frequently present in diabetics; however, a multivariable analysis confirmed that the presence of diabetes was an independent risk factor for death with regard to overall survival (HR 2.04, 95% CI 1.31–3.17, p = 0.002) [10]. A retrospective cohort study (n = 367) mirrored these findings, with diabetic patients exhibiting both poorer PFS (10.3 vs. 16.3 months) and OS (26.1 vs. 42.2 months) [4]. It has been postulated that survival differences may be partially attributable to different treatment approaches in diabetic patients due to comorbidities and dose limiting chemotherapy toxicities such as neuropathy.…”
Section: Diabetes Mellitus and Epithelial Ovarian Cancermentioning
confidence: 98%
See 4 more Smart Citations
“…This was partially attributed to co-morbidities frequently present in diabetics; however, a multivariable analysis confirmed that the presence of diabetes was an independent risk factor for death with regard to overall survival (HR 2.04, 95% CI 1.31–3.17, p = 0.002) [10]. A retrospective cohort study (n = 367) mirrored these findings, with diabetic patients exhibiting both poorer PFS (10.3 vs. 16.3 months) and OS (26.1 vs. 42.2 months) [4]. It has been postulated that survival differences may be partially attributable to different treatment approaches in diabetic patients due to comorbidities and dose limiting chemotherapy toxicities such as neuropathy.…”
Section: Diabetes Mellitus and Epithelial Ovarian Cancermentioning
confidence: 98%
“…Metformin usage is another confounding variable when assessing the correlation of diabetes to ovarian cancer. Some reports suggest that metformin reduces cancer mortality [25], whereas others have reported no survival difference among patients taking metformin [4]. …”
Section: Diabetes Mellitus and Epithelial Ovarian Cancermentioning
confidence: 99%
See 3 more Smart Citations